Novel Strategies in the Development of New Therapies, Drug Substances and Drug Carriers - Kutner, Andrzej; Brown, Geoffrey; Kallay, Enikö (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is conceived to promote synergy between research and industrial activities in the design and development of new drugs and, therefore, is not limited to any specific aspect of development. It covers the entire process from the identification of a molecular target, studies of drug-protein interactions, the modeling and optimization of the functional activity, design and chemical synthesis, biological evaluation, and the development of new pharmaceutical carriers.The original articles and reviews are focused on the design and development of new anticancer treatments, new anticancer low-molecular-weight agents as potential drug substances, and the elucidation of their mechanisms of action. The book also includes studies on novel modulators of the serotonergic system used to treat central nervous system disorders, novel agents against infectious diseases, and the development of anti-plasmodial and anti-inflammatory agents. The successful identification of new compounds for development as drug substances comes from rich sources of medicinal plants and medicinal chemistry approaches.